Simultaneous Serial Transverse Enteroplasty (STEP) in size mismatch small bowel transplantations - Frongia, Giovanni; Majlesara, Ali; Saffari, Arash; Abbasi Dezfouli, Sepehr; Günther, Patrick; Mehrabi, Arianeb (Journal of gastrointestinal surgery, 2019)
Background: Small bowel transplantation (SBTX) in children receiving larger grafts from adults can be challenging because of size mismatch. The aim of the present study was to assess whether a simultaneous serial transverse enteroplasty (STEP) can address the problem of size mismatch. Methods: Three different size ratio groups between donors and recipients were compared in a porcine model with a 14-day follow-up. The groups were size matched, size mismatched (1:3.8 weight ratio), and size mismatched + STEP (each n = 8). Results: It was technically feasible to simultaneously perform a STEP and SBTX of a mismatched intestinal segment. The postoperative clinical course was uneventful. No signs of bleeding, leakage, stenosis, or ileus were observed and the intestinal segment was well perfused at relaparotomy. Body weight decreased in all groups, but the percentage decrease was lowest in the mismatched + STEP group. Vital enterocyte masses were similar in all the groups (citrulline levels) and the nutritional status was best in the STEP group (transferrin levels, p = 0.04).ConclusionsWe have demonstrated that a simultaneous STEP and SBTX procedure is technically feasible and clinically useful in overcoming the challenges associated with size mismatched SBTX. Our short-term findings justify further investigation in a larger series to elucidate the long-term outcomes of this procedure.
First Online: 08 August 2018
Gesehen am 13.09.2019